Leaf growth pattern and morphology of Sauropus androgynus (L.) Merr. in tropical lowland - Muda, Strayker; Lakitan, Benyamin; Gustiar, Fitra; Ramadhani, Fitri; Rizar, Fitra; Nurshanti, Dora; Ria, Rofiqoh; Ratmini, Niluh; Purwanto (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2024)
Chikurmanis or katuk (Sauropus androgynus (L.) Merr.) is a traditional leafy vegetable that is consumed widely in Indonesia. The leaf is rich in vitamins, minerals, nutrients, and dietary fiber. The study aimed to investigate the leaf growth pattern and morphological characteristics of the chikurmanis cultivated in the tropical lowland ecosystem. The research was conducted on local farmland in Marga Sakti Sebelat, Bengkulu, Indonesia on December 2023 by survey method. The results showed that the leaf of chikurmanis grew in the daytime and continued to grow at nighttime as indicated in midrib length, leaf width, and foliole number. It is likely that nighttime growth become predominant in chikurmanis. The plant was a type of shrub with complete organs of stem, branch, root, flower, and leaf. The leaf was arranged as a compound leaf with many folioles in opposite positions. Midrib length (M) x leaf width (W) with a zero intercept of linear regression was the most reliable predictor of leaf area with the formula Y = 0.4964MxW (R2 = 0.9677). Keywords: chikurmanis plant; katuk; leaf area estimation; morphological trait; traditional leafy vegetable